Journal of Perinatal Medicine : Official Journal of the World Association of Perinatal Medicine (De Gruyter, 1973)
The Journal of Perinatal Medicine is a truly international forum covering the entire field of perinatal medicine. It is an essential news source for all those obstetricians, neonatologists, perinatologists and allied health professionals who wish to keep abreast of progress in perinatal and related research.